Answer:
(2, - 4 )
Step-by-step explanation:
Given the 2 equations
10x + 7y = - 8 → (1)
7x + 7y = - 14 → (2)
Subtract (2) from (1) term by term to eliminate y
(10x - 7x) + (7y - 7y) = - 8 - (- 14) , that is
3x = 6 ( divide both sides by 3 )
x = 2
Substitute x = 2 into either of the 2 equations and solve for y
Substituting into (1)
10(2) + 7y = - 8
20 + 7y = - 8 ( subtract 20 from both sides )
7y = - 28 ( divide both sides by 7 )
y = - 4
solution to the system of equations is (2, - 4 )
It depends and the measurement of the angle.
30-60-90(shown in image)
or
45-45-90
Also, sometimes you can use Pythagorean theorem
Answer:
(1.37) AUB = { 1,2,3,4,5,6}
(1.38) AUC = { 1,2,3,4,5 }
(1.39)BUC = { 1,2,3,4,5,6}
(1.40) { 2,4 }
(1.41) { 1,3,5 }
(1.42) { phi }
(1.43) AU(BUC) = { 1,2,3,4,5,6 }
(1.44) { phi }
(1.45) {1,2,3,4,5}
(1.46) { 1,2,3,4,5 }
![\huge\underline\red{Hope\:that\:helps}](https://tex.z-dn.net/?f=%5Chuge%3C%2Fp%3E%3Cp%3E%5Cunderline%5Cred%7BHope%5C%3Athat%5C%3Ahelps%7D)